Examining the Factors and Constraints Influencing the Choice of Marketing Communication Mix Elements in Rural and Community Banks (RCB’s) in Ghana - Tandoh, Isaac; Oppong Mensah, Nicholas (Test Engineering And Management, 2020)
To a very large extent, no organization can survive without paying attention or considering integrated marketing communications as a major operational activity because of the dynamism and competitiveness of the banking industry and the economy at present.The study aimed to examinethe factors and constraints influencing the choice of marketing communication mix in Rural and Community Banks (RCB’s) in Ghana. A mixed-method approached was used with 561 rural banks spread over 10 regions of Ghana chosen as the study area. Questionnaires were a major tool for data collection. Data were collected from both primary and secondary sources utilizing a structured questionnaire based on the objectives of the study. Findings from the study revealed thatmajor constraints like thehigh cost of implementation, the size of the bank, limited management capacity among others were facing the implementation of marketing communication mix strategies by the RCBs, On the determinants, the results showed that age of RCB, total deposits and a net worth significantly influence a bank to use Advertising and Personal selling as a marketing communication mix strategy with a positive coefficient of 0.1122, 0.0109 and 0.0728 at 1% and 5% levels. It was inferred that RCBsthat has been in existence for a longer period was 0.1122 likely to choose Advertising and Personal selling as a communication mix strategy at 1% compared to all the six tools. Also, a one Ghana Cedi increase in the total deposit mobilized by RCB will increase the probability that it will choose Advertising and Personal selling as a communication mix strategy by an estimated coefficient of 0.0109 at 1% compared to all the six tools.
Research Article
Keywords: Marketing Communication, Mix Elements, Rural, Community Banks, Ghana